Congregational studies in the UK: Christianity in a post-Christian context - Woodhead, Linda; Tusting, Karin (Explorations in practical, pastoral, and empirical theology, 2016)
Part One.The emerging field --Congregational studies : taking stock /Linda Woodhead, Mathew Guest and Karin Tusting --The rise of congregational studies in the USA /Arthur Farnsley --'Conference people' : congregational studies in a globalizing world /Simon Coleman --Part Two.Congregations in the UK --The effects of evangelical renewal on mainstream congregational identities : a Welsh case study /Paul Chambers --'Friendship, fellowship and acceptance' : the public discourse of a thriving evangelical congregation /Mathew Guest --Display and division : congregational conflict among Roman Catholics /Peter McGrail --Congregations, narratives and identity : a Quaker case study /Peter Collins --Congregational cultures and the boundaries of identity /Timothy Jenkins --Part Three.Theoretical and methodological issues --The messiness of studying congregations using ethnographic methods /Frances Ward --Are congregations associations? : the contribution of organizational studies to congregational studies /Helen Cameron --Priests, parish and people : reconceiving a relationship /Douglas Davies --Denominational cultures : the Cinderella of congregational studies? /Philip Richter --The significance of gender for congregational studies /Kristin Aune --Putting congregational studies to work : ethnography, consultancy and change/Martin Stringer.